Incidence and Implications of Atrial Fibrillation/Flutter in Hypertension: Insights from the SPRINT Trial - Parcha, Vibhu (Hypertension, 2020)
We evaluated the impact of intensive blood pressure (BP) control on the incidence of new-onset atrial fibrillation/flutter (AF) and the prognostic implications of pre-existing and new-onset AF in Systolic Blood Pressure Intervention Trial (SPRINT) participants. New-onset AF was defined as occurrence of AF in 12-lead electrocardiograms after randomization in participants free of AF at baseline. Poisson regression modeling was used to calculate incident rates of new-onset AF. Multivariable-adjusted Cox proportional hazard models were used to evaluate the risk of adverse cardiovascular events (composite of myocardial infarction (MI), non-MI acute coronary syndrome, stroke, heart failure, or cardiovascular death). In 9,327 participants, 8.45% had pre-existing AF, and 1.65% had new-onset AF. The incidence of new-onset AF was 4.53 per 1000-person years, with similar rates in the standard and intensive treatment arms (4.95 vs. 4.11 per 1000-person years; adjusted p=0.14). Participants with pre-existing AF [adjusted HR: 1.83 (95% CI: 1.46–2.31); p<0.001] and new-onset AF [adjusted HR: 2.45 (95% CI: 1.58–3.80); p<0.001] had a greater risk for development of adverse cardiovascular events compared to those with no AF. Participants with pre-existing AF who achieved BP <120/80 mmHg at three months continued have a poor prognosis [adjusted HR: 1.88 (95% CI: 1.32–2.70); p=0.001] compared to those with no AF. Intensive BP control does not diminish the incidence of new-onset AF in an older, high-risk, non-diabetic population. Both, pre-existing and new-onset AF have adverse prognostic implications. In participants with pre-existing AF, residual cardiovascular risk is evident even with on-treatment BP <120/80 mm Hg.